Microwave Synthesis, Characterization, and Antimicrobial Activity of Some Novel Isatin Derivatives - Ayman El-Faham; Wael N. Hozzein; Mohammad A. M. Wadaan; Sherine N. Khattab; Hazem A. Ghabbour; Hoong-Kun Fun; Mohammed Rafiq Siddiqui (Journal of Chemistry)
Three series of isatin derivatives [3-hydrazino, 3-thiosemicarbazino, and 3-imino carboxylic acid derivatives] were synthesized employing microwave irradiation. The prepared compounds were characterized by FT-IR, NMR, elemental analysis, and X-ray crystallography for derivatives 5b. The synthesized compounds were screened for antimicrobial activity against selected bacteria and fungi. The results revealed that the N-alkyl isatin derivatives were biologically active with different spectrums activity. Most of the 3-hydrazino and 3-thiosemicarbazino isatin derivatives were biologically inactive and generally the active derivatives showed weak to moderate activity mainly against Gram-positive bacteria. The imino isatin carboxylic acid derivatives (2-[4-(1-benzyl-5-bromo-2-oxoindolin-3-ylideneamino) phenyl]acetic acid, 5d) showed promising activity against all tested Gram-positive bacteria and against fungal pathogens.